Ocena rozwoju somatycznego dzieci i młodzieży z wadą słuchu (niedosłuch i głuchota) - Łuczak, Ewa (Polskie Towarzystwo Antropologiczne, 1993)
THE SOMATICAL DEVELOPMENT OF CHILDREN AND YOUTH WITH DEFECT OF HEARING (PARTIAL DEAFNESS AND DEAFNESS). The study was concerned on the relationship between the physical development and the degree hearing impairment, the etiology of hearings defect (heredity, congenital, acquired), the distemper of pregnancy and delivery and maturation rate.
THE SOMATICAL DEVELOPMENT OF CHILDREN AND YOUTH WITH DEFECT OF HEARING (PARTIAL DEAFNESS AND DEAFNESS).